Pengaruh Likuiditas, Manajemen Aset, Struktur Modal Terhadap Kinerja Keuangan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Apriani, Winda; Efni, Yulia; fiona, fiona (Politeknik Negeri Padang, 2024)
This study aims to determine the effect of liquidity, asset management and capital structure on financial performance with company size as a moderating variable among palm oil companies listed on IDX the period 2019-2023. Financial performance as the dependent variable is proxied by ROA. The independent variables include liquidity, asset management and capital structure. The population of this study is 24 palm oil companies listed on the IDX the period 2019-2023. This study employs a purposive sampling method and selects a sample of 20 palm oil companies listed on the IDX. The analysis technique utilized is Moderated Regression Analysis (MRA) using the SPSS 23 application. The result of this study is that liquidity has no effect on financial performance, asset management has an effect on financial performance, capital structure has no effect on financial performance, company size moderates the effect of liquidity on financial performance, company size does not moderate the effect of asset management on financial performance and company size moderate the effect of capital structure on financial performance.